An objective in vivo diagnostic method for inflammatory bowel disease. Issue 3 (21st March 2018) - Payne, Sophie C.; Shepherd, Robert K.; Sedo, Alicia; Fallon, James B.; Furness, John B.
Abstract : Inflammatory damage to the bowel, as occurs in inflammatory bowel disease (IBD), is debilitating to patients. In both patients and animal experimental models, histological analyses of biopsies and endoscopic examinations are used to evaluate the disease state. However, such measurements often have delays and are invasive, while endoscopy is not quantitatively objective. Therefore, a real-time quantitative method to assess compromised mucosal barrier function is advantageous. We investigated the correlation of in vivo changes in electrical transmural impedance with histological measures of inflammation. Four platinum (Pt) ball electrodes were placed in the lumen of the rat small intestine, with a return electrode under the skin. Electrodes placed within the non-inflamed intestine generated stable impedances during the 3 h testing period. Following an intraluminal injection of 2, 4, 6-trinitrobenzene sulfonic acid (TNBS), an established animal model of IBD, impedances in the inflamed region significantly decreased relative to a region not exposed to TNBS ( p < 0.05). Changes in intestinal transmural impedance were correlated ( p < 0.05) with histologically assessed damage to the mucosa and increases in neutrophil, eosinophil and T-cell populations at 3 h compared with tissue from control regions. This quantitative, real-time assay may have application in the diagnosis and clinical management of IBD.